(untitled) (Archives of Criminology, 1982)
The Penal Code of 1969 introduced in Chapter VIII a complex of regulations defining the criminal liability tfor offences committed in the conditions of special recidivism. Two categories of special recidivism were introduced: basic recidivism (Art. 60 § 1 of the Penal Code) and multiple recidivism (Art. 60 § 2 of the Penal Code). To assume the first category, the following criteria are required: 1) commission of an intentional offence similar to the previous one, 2) execution of at least 6 months of imprisonment, 3) commission of a new offence within 5 years after discharge from prison. To impute the offender the commission of an offence coming under the second category of recidivism, the following conditions are necessary: 1) conviction for at least the fourth time, in this twice under the conditions of basic special recidivism, 2) repeated commision of an intentional offence to profit financially or of hooligan character, 3) total imprisonment of at least one year, 4) commission of a new offence within 5 years after the last imprisonment. For each of those two categories of recidivism, the principles of aggravated criminal liability are fixed by the Code, and they refer to less - serious - offences only. Towards persons coming under Art. 60 § 1 and 2, imprisonment within the raised limits is adjudicated. Towards such persons, absolute suppression of suspension of the execution of penalty was formulated. The strictness of these regulations is partly diminished by Art. 61 of the Penal Code, which created the possibility to depart from the aggravation of penalty as expressed in Art. 60, in "particularly justified cases, when even the lowest penalty inflicted on the basis of Art. 60 § 1 and 2 of the Penal Code, would be incommensurably severe". The Code fights special recidivism also by providing special measures against special recidivists coming under Art. 69 § 1 and 2: protective supervision (called "supervision" further on) and social readaptation centre (called "centre" further on). The first of them - supervision - is a non isolating measure, consisting in the control of behavior of the supervised person in the conditions of liberty. It is adjudicated for a period of 3 to 5 years (Art. 63 § 1 of the Penal Code). The second measure - centre - is of isolating character. The duration of stay in the centre is not appointed beforehand in the sentence: it is at least 2 years, at most 5 years long. After 2 years, the recidivist may be discharged by the execution of penalty court if there are good reasons to presume that he will not commit any offence after discharge (Art. 65 of the Penal Code). Special measures are executed after the sentence has been served. The principles of application of the special measures differ as regards both categories of recidivists: those coming under Art. 60 § 1 of the Penal Code (called "common recidivists" further on) and those coming under Art. 60 § 2 (called further "multiple recidivists"). The organs authorized to adjudge these measures are the criminal and execution of penalty courts. Their decision as to adjudgement of them may be taken at various stages of legal and executive proceedings: in the sentence (criminal court), in the latter part of imprisonment (execution of penalty court), and during the supervision (execution of penalty court). The principles of application of the special measures by the court which is to pass judgement in the case are stated in Art. 62 of the Penal Code. According to § 1, the application of supervision is optional towards the offenders coming under Art. 60 § 1. The court is here at liberty to decide as to the possible measures, as no premises to adjudge supervision are specified by the regulation. As to the recidivists coming under Art. 60 § 2, the adjudgement of one of the two special measures is obligatory, that of supervision as a rule. The adjudgement of the centre takes place only if the court recognizes supervision insufficient to prevent recidivism (Art. 62 § 2 of the Penal Code). The second instance when decisions are taken as to the application of the special measures is the close of imprisonment of the recidivists. The rulings of the execution of penalty taken at this stage of the proceedings modify those taken previously - that is, in the sentence - as regards the application of the special measures. In the case of common recidivists, these modifications may consist in adjudgement of supervision if it was not adjudicated in the sentence (Art. 91 of the Code of Execution of Penalties), or - if the recidivist is released on probation - in the specific conditional simulation of the supervision adjudicated in the sentence (Art. 98 § 1 of the Penal Code). If the release on probation is not cancelled by the court, the adjudgement of supervision loses effect (Art. 98 § 2 of the Penal Code). In the case of multiple recidivists, the modifications which may take place in the latter part of imprisonment as regards the adjudication of the special measures always consist in substitution of a strict measure by a milder one: the penitentiary court may replace the adjudgement of the centre with supervision (Art. 103 of the Code of Execution of Penalties) or release multiple recidivists on probation. The third closing stage of proceedings when the decisions on application of special measures are taken is the execution of supervision. In this stage, the position of recidivists coming under Art. 60 § 1 and 2 of the Penal Code is identical: they can both be sent to the centre in consequence of failure of the supervision (Art. 64 of the Penal Code). Thus the adjudgement of the centre in consequence of failure of supervision serves here as a measure to discipline the execution of supervision. The present study was based on the data from criminal records of the Criminal Register and the Central Files of Convicted and Temporarily Arrested Persons. The material from these records enables one to notice the differences, as regards the data they include, between the groups of recidivists distinguished in respect of the special measure adjudicated towards them, and thus, to define initially the criteria for application of these measures. As a conclusion, an attempt was made to define the general range of adjudgement of the special measures towards recidivists regardless of the stage of proceedings in which it took place. The research was of cross-sectional character. The examined population consisted of recidivists (coming under Art. 60) from the entire country and selected to 3 random samples: the first sample included all recidivists whose sentences had become valid within the period from March 1 till April 30, 1979 (1181 persons), the second sample included all recidivists discharged from prison within the period from February 1 till March 31, 1979 (874 persons), and the third one - all recidivists whose supervision had been completed within the period from April 1 till May 31, 1979 (544 persons). There were the total of 2599 cases, from which 72 cases had been excluded because of the lack of complete data in the Criminal Register. The final populations of the separate samples were thus as follows: I - 1146 persons, II - 869 persons, III - 512 persons (the total of 2 527 persons). The collected material was then analysed, that is, the groups of persons were compared, distinguished on the grounds of the type of the special measure adjudicated towards them, for instance the group of multiple recidivists towards whom supervision had been adjudicated was compared with the group sent to the centre. The above comparisons were made for each sample separately, and within the sample - separately as regards the common and multiple recidivists. The method of representing the results reflects , the analysis scheme: each sample has been represented in a separate part of the present paper. The study is summed un by an attempt to estimate the general range of adjudgement of the special measures towards recidivists. The results of the estimation indicate that the application of the special measures towards recidivists is of a very broad range. As many an approximately a half of the common recidivists had been subjected to supervision; failure occurred as regards 40 per cent of the supervised persons, which makes about 1/5 of all common recidivists, and these persons came under the regulation providing the adjudgement of the centre in consequence of the failure of supervision. In 40 per cent of the cases the cause of the unsuccessful termination of supervision was the non-compliance with orders and duties by the supervised person, and in 60 per cent - commission of a new offence. As regards multiple recidivists, there were as few as 14 per cent of them towards whom no special measure whatever had been adjudicated, owing to adjudgements of the execution of penalty courts. Approximately 27 per cent of the multiple recidivists had been sent to the centre immediately from prison, while approximately 59 per cent had been subjected to supervision. In over a half of these cases supervision was unsuccessful, which makes about 1/3 of the multiple recidivists. The cause of the unsuccessful termination of supervision was in 2/3 of the cases commission of a new offence, and in 1/3 of the cases non-compliance with orders and duties.